Optimizing linked list-based smart contract on Ethereum with IPFS for e-book management system - Mohammadan Makhtar, Maznun Arifa; Admodisastro, Novia; Mat Isa, Mohd Anuar; Abdullah, Daniel Hafiz; Sharif, Khaironi Yatim (Politeknik Negeri Padang, 2024)
People are now widely adopting digital assets in various applications, integrating them into almost every aspect of their lives. Electronic books, or e-books, are one of the digital assets that result from the transformation of physical reading material into the digital world. Nowadays, blockchain is used in many industries because it provides immutable and transparent records. E-book publishers may take this opportunity to adopt blockchain technology for e-book data management. However, blockchain storage is limited; thus, storing the e-book files in blockchain is not recommended. A decentralized storage system, such as InterPlanetary Files Systems (IPFS), is an alternative way to store large files like e-books. IPFS can facilitate the storage of e-book files while the metadata is stored in the blockchain. The e-book metadata should be stored in a structured way for effective search and retrieval. E-book metadata could be added, deleted, and updated occasionally. Nevertheless, some data structures often struggle with dynamic collections of records. This paper proposes a linked list-based smart contract on Ethereum that integrates with IPFS for the e-book management system. We demonstrate the implementation of a linked list smart contract for insertion, deletion, update, retrieval, and traversal of the e-book’s metadata. The result shows that a linked list-based smart contract with IPFS could offer a robust solution for e-book data management. This solution provides more opportunities to explore further security and cryptography approaches toward a secure e-book management system.